Predicting Amino acid interaction network using artificial Bee colony - Enan, Mirja Shahriar; Abdullah Al Noman (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2015.